Mortality in children with cancer and SARS-CoV-2 in Latin America: A systematic review - Dorantes-Acosta, Elisa; Ávila-Montiel, Diana; Domínguez Rojas, Jesús; Parra-Nigañez, Patricia; Velasco-Hidalgo, Liliana; Arias, Sergio; Gutiérrez-Rivera, Lourdes; Juárez-Villegas, Luis; Márquez-González, Horacio (Frontiers in Pediatrics, 2022)
The new COVID-19 disease is caused by a novel coronavirus (SARS-CoV-2), that probably originated in Wuhan, China, and has currently infected 505,817,953 people and caused 6,213,876 deaths in the world.On the American continent, 152,265,980 cases and 2,717,108 deaths have been reported to WHO (World Health Organization) The Latin America and the Caribbean (LAC) region presents an epidemiological challenge due to its population's heterogeneity and socioeconomic inequality. Children aged 5 to 14 make up 6.3% of all global cases. A particularly vulnerable population is that of children with cancer, and their mortality from COVID-19 has been reported to be 3.6% globally. This work aimed to study the lethality of SARS-CoV-2 infection in children with cancer in the Latin American region. Our objective was to systematically review published scientific literature and search hospital databases in Latin America to explore mortality in this region. A median of mortality of 9.8% was found in the articles analyzed. In addition, we collected five databases from Latin American hospitals. We concluded that there was an underestimation in the mortality registry of this group of patients in the analyzed region. Therefore, although the causes are unknown, it is necessary to strengthen the case-reporting system to determine the reality in complex and particular areas such as Latin America.